Changes in the salivary biomarkers induced by an effort test - de Oliveira, V. N.; Bessa, A.; Lamounier, R. P. M. S.; de Santana, M. G.; de Mello, M. T.; Espindola, F. S. (International Journal of Sports Medicine, 2010)
Physical exercise induces biochemical changes in the body that modify analytes in blood and saliva among other body fluids. This study analyzed the effect of an incremental effort test on the salivary protein profile to determine whether any specific protein is altered in response to such stress. We also measured thresholds of salivary alpha amylase, total salivary protein and blood lactate and searched for correlations among them. Twelve male cyclists underwent a progressive test in which blood and saliva samples were collected simultaneously at each stage. The salivary total protein profile revealed that physical exercise primarily affects the polypeptide corresponding to salivary alpha-amylase, the concentration of which increased markedly during the test. We observed thresholds of salivary alpha-amylase (sAAT), total salivary protein (PAT) and blood lactate (BLT) in 58%, 83% and 100% of our sample, respectively. Pearson's correlation indicates a strong and significant association between sAAT and BLT (r= 0.84, p<0.05), sAAT and PAT (r= 0.83, p<0.05) and BLT and PAT (r= 0.90, p<0.05). The increased expression of the salivary alpha-amylase (sAA) polypeptide suggests that sAA is the main protein responsible for the increase in total protein concentration of whole saliva. Therefore, monitoring total protein concentration is an efficient tool and an alternative noninvasive biochemical method for determining exercise intensity.